Effectiveness Of Learning Through The Application Of Technology Of Education In The Digital Era - Janiah; Harapan, Edi; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
In this research, the problem that is being researched is the use of learning in the digital age. The center of the study focuses on teachers' use of information technology in learning. ai The aim of this research is to: understand the application of IT and the application of IT to the effectiveness of learning in MTs Se-Kabupaten Musi Banyuasin. This research method is a quantitative descriptive method for 5 MTs with a sample of 120 teachers in the Musi Banyuasin district. Personal Product Moment Correlation is the correlation analysis method used. The results of research in MTs in Musi Banyuasin district showed that: the variable implementation of information technology promotes the effectiveness of learning positively and significantly Supports learning potential in the MTs Se-Kabupaten Musi Banyuasin